Two General Concepts of Depreciation - Johnson, Orace (Journal of Accounting Research, 1968)
The analysis of methods begins with the problem of definition. Many definitions are possible. Not all are equally useful. This article offers two general concepts that are defined according to their logical consequences. One of them enables us to view many common patterns (such as straightline or sum-of-digits) as particular results of the same general method. The two concepts to be compared are labeled conventional depreciation and time-adjusted depreciation. Each has its distinctive characteristic and a different effect on reported net income. Throughout this article, I shall assume economic rationality and perfect foresight with all expectations fully realized. For simplicity, taxes will be ignored.